A new remarkable genus and species of Mantispidae (Neuroptera) from the earliest Eocene of Denmark - Makarkin, Vladimir N.; Perkovsky, Evgeny E. (Zootaxa, 2026)
Heiemantispa storozhenkoi gen. et sp. nov. (Neuroptera: Mantispidae) is described from the earliest Eocene Fur Formation, Denmark. The genus is distinguished from others of the family by a combination of forewing character states: a simple CuP (unique in Drepanicinae, if it belongs to that subfamily) and a basally unfused M and R. The venation of Heiemantispa gen. nov. is most similar to that of Protheristria Makarkin et al., 2025, also from the Fur Formation. Both genera are known only from incomplete wings of their type species, the venation of which does not allow them to be confidently assigned to either the subfamily Drepanicinae or Calomantispinae.